Հարկային բեռի կրճատման անհրաժեշտությունը ՀՀ գյուղատնտեսության ոլորտում - Մարտիրոսյան, Գևորգ (ՀՀ ԳԱԱ ՏԻ)
Сельское хозяйство является единственной отраслью экономики, обеспечивающей решение проблем, связанных с самообеспечением населения государства. Процесс сбора налогов для населения, занимающегося сельско- хозяйственной деятельностью в РА, должен быть реализован с 1 января 2025 года, однако принципы и инструменты, используемые государством для реализации этого процесса, пока неизвестны. В этой отрасли экономики РА до сих пор существует ряд не получивших своего решения проблем, которые мы рассмотрели в рамках статьи. В РА существуют возможности и перспективы развития сельского хозяйства, которых можно достичь в результате государственного контроля и ответственного отношения населения. Agriculture is the only sector of the economy that provides solutions to problems related to the food self-sufficiency of the population. The process of collecting taxes from the citizens engaged in agriculture activities in RA should be implemented from January 1, 2025, but the principles and tools of the implementation are not yet known. This sector of the RA economy still has several development issues that have not received their solutions, and which were addressed in the framework of this article. There are opportunities and prospects for the development of agriculture in RA, which can be achieved as a result of state regulation and the responsible attitude of the population. The relevance of the article lies in the fact that the increase in the tax burden on the output of agriculture production in the RA may negatively affect the attractiveness of that sector. The main goal of the article is to propose legislative changes related to the tax burden in RA that serve the development prospects of the sector and the investment policy. To achieve that goal, the following tasks were set: to study the development process and development prospects of agriculture in the RA and propose rates of taxation of the outputs of agriculture production. The goal of the article was achieved with the help of data description, collection, comparison and analytical methods.
Keywords: Գյուղատնտեսություն